Flower description and fertility of the main Tunisian almond cultivars - Gouta H.; Ouni R.; Mars M. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
The almond Prunus dulcis (Mill.) D.A. Webb is an old edible nut that is present in Tunisia with a large phenotypic and genetic diversity of cultivars and landraces. However, no much investigation has treated the characterization of the local cultivars regarding flower description and fertility parameters. This study is dealing with the evaluation of the almond genetic diversity on the basis of some parameters related to flower characteristics. Also, the quality of pollen as well as the fructification rates for self and cross-pollination were studied in order to differentiate among genotypes according to their degree of self compatibility or incompatibility. Results showed a great intraspecific genetic diversity. Analysis and observations allowed us to distinguish some particular genotypes such as ‘Zahaf’ which is characterized by its largest flower size. Also it was concluded that ‘Achaak 2’ has the highest potential of fertility (80%) and a considerable fruit bearing and productive capacities. ‘Mahsouna’ and ‘Tlili 8’ presented the highest rates of fruit set when self-pollinated and as a consequence showed a tendency for self-compatibility.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)